Evaluation of Entrepreneur Potential of Karaganda Region - KULMAGAMBETOVA, Zhanargul Zh.; BAIBOSSYNOV, Serikzhan B.; LISOVA, Natalya A.; RAMASHOVA, Aissulu N.; KOSHEBAYEVA, Gaukhar K. (Journal of Advanced Research in Law and Economics, 2018)
The relevance of the research topic is determined by the activation of the entrepreneurial activity process. Industry is the main activity of the Karaganda region in terms of employment. The main goal of the work is to assess the entrepreneurial potential of the Karaganda region. To achieve this goal, the author used theoretical methods, which include analysis, synthesis, and comparison. The author also found that the largest number of inactive population is in Karaganda and it is 127.210 people. The Karaganda region is part of a group of regions with a high level of investment potential, together with Almaty, Atyrau region, Astana, and East Kazakhstan region. Analyzing the situation in the region it was established that the economy of the region is mainly supported by large enterprises, which, as a rule, are city-forming. It is determined that entrepreneurs are independent of external factors and they primarily rely on themselves in the present situation.